Simulator driving performance, subjective sleepiness and salivary cortisol in a fast-forward versus a slow-backward rotating shift system - De Valck, Elke; Quanten, Stijn; Berckmans, Daniël; Cluydts, Raymond (Scandinavian Journal of Work, Environment & Health, 2007)
' ' OBJECTIVES ': 'The objectives of this study were to examine simulator driving and subjective sleepiness after morning, afternoon, and night shifts and to compare these differences, as well as objective stress, between a fast-forward and a slow-backward rotating shift system. ' ' METHODS ': 'The participants were male volunteers working in a chemical plant, 18 in a slow-backward rotating system and 18 in a fast-forward rotating system. All of the participants performed a driving simulator test and subjectively estimated sleepiness after a night, afternoon, and morning shift. Salivary cortisol samples, as indicators of the objective stress level, at the beginning of the workweek—after the second morning shift—were compared between the two rotating shift systems. ' ' RESULTS ': 'Lane drifting was higher after a night shift than after an afternoon shift. No effect of rotation system on driving performance could be shown. The subjective sleepiness scores were significantly higher in the slow-backward rotating group than in the fast-forward rotating group. A significant effect of shift type was also observed, with lower levels of sleepiness after the afternoon shift than after the morning and night shifts. Salivary cortisol samples taken at the start of the workweek did not significantly differ between the fast-forward and the slow-backward rotation shift systems. ' ' CONCLUSIONS ': 'This study indicated that shift type is more important than shift schedule—direction and speed of rotation—in determining driving performance. Performance seemed to be threatened mostly by a night shift and the least by an afternoon shift. In contrast, subjective sleepiness also differed between rotation groups and indicated an advantage of the fast-forward rotation system. The exploratory salivary cortisol measurements suggested that the shift systems studied do not differ in the level of stress they induce, that is to say at the beginning of the workweek.
Keywords: alertness; backward-rotating shift system; circadian rhythm; forward-rotating shift system; salivary cortisol; shift schedule; shift work; simulator driving; sleep; stress; subjective sleepiness; traffic safety